Children's Conceptions of Intelligence. What is role of Executive Functions and Self-regulation? - Pino Muñoz, Mónica M. (2019)
Intelligence is a construct of notable impact in our sociocultural context, related to a wide range of conceptual and operational definitions which originate positions that highlights cognitive and abstract elements and emotional and social skills, as well was perspectives that are focused on processes underlying the intelligent performance, such as in the case of executive functions (EFs), which are configured as cognitive processes that make it possible the self-regulation (Miyake & Friedman, 2012). Similarly, there are approaches that give intelligence a relevant and predictive role of school performance, an aspect strengthened by the psychometric perspective, where the concept of intelligence has been closely linked to learning. In this line, we also find the classical perspective of crystallized Intelligence of Cattell (1943), which refers to the knowledge acquired through educational and cultural processes. The aim of this study is to know the conceptualizations of intelligence of children aged 8-12, the features they give to them, and the assessment of their own intellectual capacities. The data analysis was carried out through the grounded theory and the results mainly show that participants attribute components referred to the management of school contents and quantitative performance to intelligence. Moreover, the answers show elements related to EFs and self-regulation not only when considering the meaning of the construct, but also while characterizing and evaluating the intelligence performance.